Melanie Ender - Folie, Sabine 1962-; Vela García, Mariel; Lein, Cornelia 1988- (VfmK Verlag für moderne Kunst GmbH, 2024)
Skin, that membrane that separates the inside from the outside, absorbs particles of what it has touched. When there is a high concentration of metals in the soil, snails will accumulate some of the material in their viscera, or green oxidized hues will color someone’s finger where once there was a ring. These traces represent contacts, transmutations of matter that appear almost imperceptible. In grasping the swift motions of copper and the slowness in a trail of mucus, Melanie Ender’s work is one of encounters and meeting places, of matter caught in a state of continuous flux. (Mariel Vela García) The publication offers a first monographic overview of the work of Vienna-based artist Melanie Ender. In addition to a foreword by Sabine Folie, a conversation between Cornelia Lein and Melanie Ender as well as an essay by Mariel Vela Garcia, the book brings together sculptures, poems and installations from the years 2016-2023
Auflage: 500 Exemplare
Keywords: Ender, Melanie -- 1984-; Objektkunst; Zeichnung; Plastik; Bildband